Studi Pengujian Karakteristik Minyak Nabati Terhadap Tegangan Tembus Sebagai Alternatif Pengganti Minyak Trafo - Samsurizal Samsurizal; Andi Makkulau; Siti Amaliatu Zahra (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2022)
The increase in the use of mineral oil or petroleum as insulation for electrical equipment is increasing every year due to the function to withstand the breakdown voltage on electrical equipment, namely the transformer, this mineral oil can withstand a breakdown voltage of >30 KV/2.5mm according to the standards set by the PLN. Based on data obtained on January 9, 2021, from the Indonesian Ministry of Energy and Mineral Resources, it is stated that Indonesia's oil reserves will run out in 9.5 years with the assumption that no new reserves will be discovered in the future. This research was conducted to test several vegetable oils, to be able to reduce or replace the function of mineral oil which is getting thinner every year. The method used in this test is a direct test method with vegetable oils such as candlenut oil, castor oil, and coconut oil on the breakdown voltage. In the research and testing that has been done on coconut cooking oil, candlenut oil and castor oil, the breakdown voltage values obtained are 12.93 kV, 14 kV, and 68.73 kV. So it can be said based on the results of the tests carried out that castor oil has a breakdown voltage of 68.73 kV, it means that it is possible to be used as an alternative to existing transformer oil, because it has a breakdown voltage according to the standards set by PLN.